COMPARATIVE STUDY DECISION SUPPORT SYSTEM AHP AND SAW METHOD IN TENDER PROCESS TV TRANSMISSION STATIONS - Sutoyo, Purwono; Dewi Nusraningrum (Dinasti Publisher, 2020)
This research compares two methods of Decision Support System, namely: Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW), by taking a case study regarding the tender process of MNC television transmission stations for Denpasar locations. Based on four main criteria, namely: price, quality, service and reliability in determining the winner of the tender followed by three alternative participants (PT. Axx, PT. Nx and PT. Lxx). Sampling in this study uses a purposive sampling or judgment sampling method based on the consideration of the personnel (informants) involved directly or indirectly in the tender process. The final result of the calculation using the AHP method shows that the alternative priorities ranked 1st to 3rd are PT. Axx total value of 0.592, PT. Nx total value of 0.274 and PT. Lxx total value of 0.134. While the calculation using the SAW method obtained an alternative priority ranking 1st to 3rd is PT. Axx total value of 0.95325, PT. Nx total value of 0.92185 and PT. Lxx total value is 0.71585. Quality criteria are the main priority in the selection of vendors, reliability, service and price criteria are the next priorities. The final score results obtained from various calculations are not the same, which indicates that the maturity of the data that is processed to become accurate information is different. The SAW method is more widely used because the calculation process is easier to understand, fast and simple than the AHP method. Whereas AHP is superior in data accuracy, because the value of criteria weights is not arbitrarily determined, but is generated based on calculations.